2014
DOI: 10.2108/zs130234
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunochemical Characterization of Two Discrete Vitellogenin Proteins and Their Derived Lipovitellins in the Inshore Hagfish (Eptatretus burgeri)

Abstract: Vitellogenesis has been extensively studied in oviparous vertebrates, including teleost fishes, while not much is known with regard to jawless hagfishes, modern representatives of the most primitive vertebrate class. This study aimed to characterize vitellogenin (Vtg) and yolk protein (YP) in the inshore hagfish (Eptatretus burgeri) as an initial step to understand vitellogenesis in this species. A putative Vtg fraction was purified from the serum of female hagfish by combinations of hydroxylapatite and ion-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Phylogenetic analyses of vertebrate Vtgs suggested that the phosvitinless VtgC is a neo-functional product of the second whole-genome duplication that occurred subsequent to the divergence of jawless (Agnathans) and jawed (Gnathostomes) vertebrates (Finn & Kristoffersen, 2007;Prowse & Byrne, 2012). The presence of phosvitin in the Vtgs of invertebrates (such as the mosquito), agnathan fishes, and the Indonesian coelacanth (Latimeria menadoensis) (Canapa et al, 2012;Chen, Sappington, & Raikhel, 1997;Nishimiya et al, 2014;Sharrock et al, 1992)-indicates that this domain was lost after the divergence of ray-finned (Actinopterygians) and lobe-finned (Sarcopterygians) fishes.…”
mentioning
confidence: 99%
“…Phylogenetic analyses of vertebrate Vtgs suggested that the phosvitinless VtgC is a neo-functional product of the second whole-genome duplication that occurred subsequent to the divergence of jawless (Agnathans) and jawed (Gnathostomes) vertebrates (Finn & Kristoffersen, 2007;Prowse & Byrne, 2012). The presence of phosvitin in the Vtgs of invertebrates (such as the mosquito), agnathan fishes, and the Indonesian coelacanth (Latimeria menadoensis) (Canapa et al, 2012;Chen, Sappington, & Raikhel, 1997;Nishimiya et al, 2014;Sharrock et al, 1992)-indicates that this domain was lost after the divergence of ray-finned (Actinopterygians) and lobe-finned (Sarcopterygians) fishes.…”
mentioning
confidence: 99%